2024
DOI: 10.1007/s00701-024-05929-y
|View full text |Cite
|
Sign up to set email alerts
|

Critical ICP thresholds in relation to outcome: Is 22 mmHg really the answer?

Agnes C. Riparbelli,
Tenna Capion,
Kirsten Møller
et al.

Abstract: Purpose Intensive care for patients with traumatic brain injury (TBI) aims, among other tasks, at avoiding high intracranial pressure (ICP), which is perceived to worsen motor and cognitive deficits and increase mortality. International recommendations for threshold values for ICP were increased from 20 to 22 mmHg in 2016 following the findings in a study by Sorrentino et al., which were based on an observational study of patients with TBI of averaged ICP values. We aimed to reproduce their app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…For borderline ICP values like 18-22 mm Hg (and possibly lower values in selected cases) the need for additional data becomes evident, since allowing ICP to remain beyond individual safety thresholds may carry inadvertent consequences [56]. This is supported by the recent work from Riparbelli et al [4], in which a cohort of more than 300 patients found 18 mm Hg as a threshold associated with mortality and unfavorable outcomes.…”
Section: Adherence To Icp Management Guidelinesmentioning
confidence: 96%
See 1 more Smart Citation
“…For borderline ICP values like 18-22 mm Hg (and possibly lower values in selected cases) the need for additional data becomes evident, since allowing ICP to remain beyond individual safety thresholds may carry inadvertent consequences [56]. This is supported by the recent work from Riparbelli et al [4], in which a cohort of more than 300 patients found 18 mm Hg as a threshold associated with mortality and unfavorable outcomes.…”
Section: Adherence To Icp Management Guidelinesmentioning
confidence: 96%
“…Our understanding of intracranial pressure (ICP), a critical indicator of brain health, is continuously evolving [1], with satisfactory evidence supporting its monitoring as a means of outcome improvement [2,3]. However, both the safety limits and therapeutic thresholds for managing and treating ICP are still debatable [4,5], although the current recommendation is based on 22 mm Hg [6]. Several notable trials investigating traumatic brain injury (TBI), whether targeting ICP alone [7] or in combination with brain oximetry [8], employing various therapy strategies, such as decompressive craniectomy [9,10], hypothermia [11], and others, have highlighted the ongoing need for further advancement in outcome improvement.…”
Section: Introductionmentioning
confidence: 99%